Diverse, Novel Mycoviruses From the Virome of a Hypovirulent Sclerotium rolfsii Strain - Zhu, Jun Zi; Zhu, Hong Jian; Gao, Bi Da; Zhou, Qian; Zhong, Jie (Frontiers in Plant Science, 2018)
Sclerotium rolfsii, which causes southern blight in a wide variety of crops, is a devastating plant pathogen worldwide. Mycoviruses that induce hypovirulence in phytopathogenic fungi are potential biological control resources against fungal plant diseases. However, in S. rolfsii, mycoviruses are rarely reported. In a previous study, we found a hypovirulent strain carrying a diverse pattern of dsRNAs. Here, we utilized the RNA_Seq technique to detect viral sequences. Deep sequencing, RT-PCR and Sanger sequencing validation analyses revealed that this strain harbors various new viral species that show affinity to the distinctly established and proposed families Benyviridae, Endornaviridae, Fusariviridae, Hypoviridae, and Fusagraviridae. Moreover, some viral sequences that could not be assigned to any of the existing families or orders were also identified and showed similarities to the Alphavirus, Ourmiavirus, phlegivirus-like and Curvularia thermal tolerance virus-like groups. In addition, we also conducted deep sequencing analysis of small RNAs in the virus-infecting fugal strain. The results indicated that the Dicer-mediated gene silencing mechanism was present in S. rolfsii. This is the first report of viral diversity in a single S. rolfsii fungal strain, and the results presented herein might provide insight into the taxonomy and evolution of mycoviruses and be useful for the exploration of mycoviruses as biocontrol agents.